Hubungan antara tingkat pengetahuan karies gigi dengan indeks DMF-T pada siswa kelas V SD Negeri Walitelon Utara Temanggung - Nur Hasanah, Siti; Ta’adi, Ta’adi; Khasanah, Furaida (Journal of Oral Health Care, 2019)
Ages 5 to 12 years are the age group that is susceptible to caries. The high caries prevalence rate of 42.6% reflects the low level of knowledge about dental health. The knowledge about dental and oral health will indirectly influence the health of the teeth and mouth so that it can prevent dental caries. The knowledge is used as a self-education to achieve the optimal dental and oral health. To find out the relationship between the dental caries knowledge level with the DMF-T Index. This research used the analytic survey with the cross-sectional data collection. This research was conducted in December 2018 to January 2019. The population in this research was the 5th grade students of the North Walitelon State Elementary School. The samples of this research were the 39 5th-grade students with the total sampling. The research instruments were questionnaire and the DMF-T Index examination format. The data were analyzed using the Kendall’s tau-b correlation test. The level of knowledge with the good criteria had a low DMF-T Index of 92.3%, the moderate was as much as 2.6%, and the fair knowledge level had a low DMF-T Index of 5.1%. The Kendall’s tau-b test results showed a relationship between the dental caries knowledge level and the DMF-T Index, and the obtained p value = 0,000 (p < 0.05). The high knowledge level of dental caries affected the results of the DMF-T index.